Meeting standards for die heat treatment. (December 2014) - Korecki, M.; Olejnik, J.; Kula, P.; Wołowiec, E.
Abstract : Problems with ensuring the quality of large tools have led to the creation of several processing standards the most widely applied of which is from NADCA. The basis of this standard is briefly described along with the vacuum furnace equipment capable of achieving it. Results of experimental validation show that this equipment can easily meet the current and future needs of the tooling industry.